Current Trends in Tamil Cinema and its Impact on Audience - Raju, M (Journal of Advanced Research in Journalism & Mass Communication, 2018)
The “CINEMA” is a mesmerizing word for the Tamil Audience and it is ruling the hearts and houses for more than 100 years. The larger than life images have played a major role in the socio, political and cultural lives of the people of Tamil Nadu. The images have participated in all emotion of the audience, when the nation was fighting for freedom, the images have spelled “Vanthe Matharam”, during the festival the images have sung “Unnaikandu Naan Aada… Ullasam Pongum inba Deepavali”, during the world war the images have narrated “Andhanal”. When television was entered, the cinema has embarrassed and made television as supplement screen. When people had communal riot, the cinema presented “BOMBAY”, at the time of water scarcity the screen offered “Thanneer Thanner”, when we were at romantic mood it screened “16 Vayathinile”, to empower the women and to criticize the male domination it showed “Pudhumai Pen”, it punished the pannyar in Uthiri Pookkal, exposed the life of the innocent tribals in “Mullum Malarum” it brought the historical characters to proximity like “Veera Pandiya Kattabomman”, “Raja Raja Cholan”, It was created docu-fiction on the lives of ethnic groups as “Devar Magan”, “Madhurai Veeran”, “Chinna Gowndar” and “Kala”. Above all the cinema has provided five Chief Ministers to Tamil Nadu assembly. After the implementation of New Economic policy the cinema has faced many obstacles. The satellite television has offered more than 100 channels, the conventional cinema has changed from celluloid to digital, sports become as the core entertainment for the young ones, family audiences have moved away from theatre, ticket prices went up, Mobile brought the digital content to the palm of young audience in spite of all these challenges, the cinema multiplexes have increased, the film productions also have increased in numbers, new film makers are coming in and the Tamil film business have widened its wings to the international spear. The Tamil films are continued to be in the goodwill of Tamil People with the changing screen formats provided by the AMAZON PRIME and the NETFLIKS. How to cite this article: M Raju. Current Trends in Tamil Cinema and its Impact on Audience. J Adv Res Jour Mass Comm 2018; 5(4): 174-177. DOI: https://doi.org/10.24321/2395.3810.201836